Juridical Analysis of the Application of Administrative and Criminal Sanctions to Tax Evasion Cases - Loso Judijanto; Abd Razak Musahib (Journal of Strafvordering Indonesian, 2025)
Taxes are the main instrument in the country's financial system because they function as a source of revenue to support national development. However, tax evasion practices are still rampant and cause significant fiscal losses, requiring effective law enforcement. In the context of Indonesian tax law, tax avoidance can be subject to administrative and criminal sanctions in accordance with the provisions of Law Number 28 of 2007 concerning General Provisions and Tax Procedures (KUP Law). Administrative sanctions function as the main instrument that is both preventive and repressive through the mechanism of fines, interest, or increases in taxes owed. However, in cases with the impact of large losses and intentional elements, relevant criminal sanctions are applied as the ultimate remedium. Reform through Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (HPP Law) strengthens aspects of legal certainty, affirms the principle of ultimum remedium, and increases the authority of tax authorities while still paying attention to the protection of taxpayer rights. This study uses a normative juridical method by examining positive norms, the principle of legality, the principle of proportionality, and the principle of justice in the application of sanctions. The results of the analysis show that the integration of administrative, criminal, and regulatory sanctions is able to create a fairer, more transparent, and sustainable tax system, while maintaining legal legitimacy and public trust